Advancing Industries with AI: The applications being transformational include: Healthcare, powering the Petroleum industry, Handling fraud, Cybersecurity, and Conversational AI - Ali, Mohammad (Information Technology and Science (ITScience), 2024)
Today, AI is becoming integrated into more and more sectors of human activity, providing new approaches to a number of traditional problems, and improving multiple aspects of business and industrial processes, decision-making, and customer interactions. This paper explores the applications of AI across five key sectors: health care, petroleum, fraud detection, cybersecurity, and conversational designing. Using AI in healthcare, diagnostics and treatment have been transformed together with improvement of patients’ care, early disease identification and better clinical outcomes. AI is applied in enhancement of exploration, production and refinery of petroleum products in the industry while enhancing sustainability. In fraud detection, AI systems thus offer capability to analyze large datasets in real time to reduce and prevent frauds in banking and insurance industries as well as e-commerce businesses. AI in cybersecurity strengthens threat identification, supports automatic management of preventive measures, and offers risk prognosis, with improved protection measures against cyber threats. And, lastly, conversational AI is emerging in the shape of technologies such as Chatgpt that help enhance customer experience and generate content. However, the increasing number of users of artificial intelligence technologies has a number of problems related to advisor ethics, data protection, system openness, and the dynamic nature of threats. While AI technologies mature, their adoption in these industries raises important questions about ethics, security and legal requirements with a view of mainstream proper and democratic development of these technologies. Raising the question of how to advance AI in the face of its problems, the future of AI remains in the effectiveness of using it as a tool for improving technology’s capabilities and for providing solutions which will make the technology more effective, secure, and more accessible in a number of years.